Liquiritin Attenuates Pathological Cardiac Hypertrophy by Activating the PKA/LKB1/AMPK Pathway - Aiyasiding, Xiahenazi; Liao, Hai-Han; Feng, Hong; Zhang, Nan; Lin, Zheng; Ding, Wen; Yan, Han; Zhou, Zi-Ying; Tang, Qi-Zhu (Frontiers in Pharmacology, 2022)
Background: Liquiritin (LQ) is one of the main flavonoids extracted from the roots of Glycyrrhiza spp., which are widely used in traditional Chinese medicine. Studies in both cellular and animal disease models have shown that LQ attenuates or prevents oxidative stress, inflammation, and apoptosis. However, the potential therapeutic effects of LQ on pressure overload-induced cardiac hypertrophy have not been so far explored. Therefore, we investigated the cardioprotective role of LQ and its underlying mechanisms in the aortic banding (AB)-induced cardiac hypertrophy mouse model. Methods and Results: Starting 3 days after AB surgery, LQ (80 mg/kg/day) was administered daily over 4 weeks. Echocardiography and pressure-volume loop analysis indicated that LQ treatment markedly improved hypertrophy-related cardiac dysfunction. Moreover, hematoxylin and eosin, picrosirius red, and TUNEL staining showed that LQ significantly inhibited cardiomyocyte hypertrophy, interstitial fibrosis, and apoptosis. Western blot assays further showed that LQ activated LKB1/AMPKα2/ACC signaling and inhibited mTORC1 phosphorylation in cardiomyocytes. Notably, LQ treatment failed to prevent cardiac dysfunction, hypertrophy, and fibrosis in AMPKα2 knockout (AMPKα2−/−) mice. However, LQ still induced LKB1 phosphorylation in AMPKα2−/− mouse hearts. In vitro experiments further demonstrated that LQ inhibited Ang II-induced hypertrophy in neonatal rat cardiomyocytes (NRCMs) by increasing cAMP levels and PKA activity. Supporting the central involvement of the cAMP/PKA/LKB1/AMPKα2 signaling pathway in the cardioprotective effects of LQ, inhibition of Ang II-induced hypertrophy and induction of LKB1 and AMPKα phosphorylation were no longer observed after inhibiting PKA activity. Conclusion: This study revealed that LQ alleviates pressure overload-induced cardiac hypertrophy in vivo and inhibits Ang II-induced cardiomyocyte hypertrophy in vitro via activating cAMP/PKA/LKB1/AMPKα2 signaling. These findings suggest that LQ might be a valuable adjunct to therapeutic approaches for treating pathological cardiac remodeling.